Preventing Electoral Fraud in Indonesia: Protecting the Social Security of Election Management Personnel - Riwanto, Agus; Suryaningsih, Sukarni; Firmandiaz, Viddy (Jurnal Media Hukum, 2000)
Indonesia’s Election Management Bodies (EMBs), constitutionally mandated to manage legislative and presidential elections, face substantial risks, including accidents and fatalities. However, their social security rights are often overshadowed by the focus on civil servants and private-sector workers. This study, employing normative legal research, urges the need for state protection of EMBs’ social security rights, drawing on secondary data sources. EMBs should receive comprehensive work-related accident benefits, death benefit programs, and old-age protection schemes from the Workers Social Security Agency (BPJS Ketenagakerjaan). The legal basis for these social security rights can be found in several legislative provisions, including the Indonesian 1945 Constitution, the National Social Security System Law, and other related regulations. Recognizing EMBs as state-serving workers is a crucial step in safeguarding their social security rights. This recognition is not merely a matter of legal interpretation; it is a necessity to ensure a fair and secure electoral environment. By ensuring that EMBs are accorded the same rights and protections as other workers, the state can create a more equitable electoral process and reinforce the integrity of its democratic institutions.